Early lens extraction with intraocular lens implantation for the treatment of primary angle closure glaucoma: an economic evaluation based on data from the EAGLE trial. Issue 1 (13th January 2017) - Javanbakht, Mehdi; Azuara-Blanco, Augusto; Burr, Jennifer M; Ramsay, Craig; Cooper, David; Cochran, Claire; Norrie, John; Scotland, Graham
Abstract : Objective: To investigate the cost-effectiveness of early lens extraction with intraocular lens implantation for the treatment of primary angle closure glaucoma (PACG) compared to standard care. Design: Cost-effectiveness analysis alongside a multicentre pragmatic two-arm randomised controlled trial. Patients were followed-up for 36 months, and data on health service usage and health state utility were collected and analysed within the trial time horizon. A Markov model was developed to extrapolate the results over a 5-year and 10-year time horizon. Setting: 22 hospital eye services in the UK. Population: Males and females aged 50 years or over with newly diagnosed PACG or primary angle closure (PAC). Interventions: Lens extraction compared to standard care (ie, laser iridotomy followed by medical therapy and glaucoma surgery). Outcome measures: Costs of primary and secondary healthcare usage (UK NHS perspective), quality-adjusted life years (QALYs) and the incremental cost-effectiveness ratio (ICER) for lens extraction versus standard care. Results: The mean age of participants was 67.5 (8.42), 57.5% were women, 44.6% had both eyes eligible, 1.4% were of Asian ethnicity and 35.4% had PAC. The mean health service costs were higher in patients randomised to lens extraction: £2467 vs £1486. The mean adjusted QALYs were also higher with early lens extraction: 2.602 vs 2.533. The ICER for lens extraction versus standard care was £14 284 per QALY gained at three years. Modelling suggests that the ICER may drop to £7090 per QALY gained by 5 years and that lens extraction may be cost saving by 10 years. Our results are generally robust to changes in the key input parameters and assumptions. Conclusions: We find that lens extraction has a 67–89% chance of being cost-effective at 3 years and that it may be cost saving by 10 years. Trial registration number: ISRCTN44464607 ; Results.